2015
DOI: 10.3368/aoj.65.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Divergence Insufficiency Esotropia: Surgical Treatment

Abstract: Divergence insufficiency esotropia, or acquired comitant esotropia that is at least 10Δ larger at distance than at near, is most often seen in older adults, and may also be known as “age-related distance esotropia.” Surgical treatment is often indicated for patients who do not tolerate prism therapy, or for those with large angles of esotropia. Surgical treatments have evolved with our understanding of the disease-state. Currently, accepted treatments include lateral rectus resection and medial rectus recessio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In fact, previous studies have reported no benefit. 94 Lateral rectus resection 95 as well as medial rectus recession 95,96 have proven successful at resolving divergence insufficiency esotropia. Surgery can be performed bilaterally or unilaterally.…”
Section: P353mentioning
confidence: 99%
“…In fact, previous studies have reported no benefit. 94 Lateral rectus resection 95 as well as medial rectus recession 95,96 have proven successful at resolving divergence insufficiency esotropia. Surgery can be performed bilaterally or unilaterally.…”
Section: P353mentioning
confidence: 99%